Pengaruh Keselamatan Kerja, Kesehatan Kerja Dan Disiplin Kerja Terhadap Kinerja Cleaning Service di Rumah Sakit Umum Daerah Nganjuk - Rulan Aprestiandy Sonya (Universitas Islam Kadiri, 2020)
Nganjuk District General Hospital has entrusted the cleanliness of the building and work area to outsourced cleaning service personnel from third parties. The number of cleaning service staff is seventy-one, consisting of 4 cleaning service coordinators or supervisors, twenty-two for yard and park cleaners and outpatients, forty-five for inpatients. Their work schedule is divided into three shifts, i.e. morning, noon and night including red dates or national holidays. In a hospital organizational structure, the performance of cleaning service personnel is under the responsibility of the Environmental Sanitation Installation. This study aims: (1) To find out and analyze the effect of work safety on cleaning service performance. (2) To find out and analyze the effect of occupational health on the cleaning service performance. (3) To find out and analyze the effect of work discipline on the cleaning service performance. (4) To find out and analyze the influence of occupational safety, occupational health and work discipline on the performance of cleaning services. (5) To find out and analyze among the variables of occupational safety, occupational health and work discipline which have the most dominant influence. This study uses a quantitative analysis method, namely analysis of data that has been given a score in accordance with a predetermined measurement scale using statistical formulas. The analysis used is data in the form of numbers. While the data analysis method uses: (1) descriptive data analysis, (2) classic assumption test, (3) and inferential statistical analysis.The results showed that: (1) The effect of work safety partially has a significant effect on cleaning service performance. (2) The effect of occupational health partially has a significant effect on cleaning service performance. (3) The effect of work discipline partially has a significant effect on cleaning service performance. (4) The effect of work safety, occupational health and work discipline simultaneously have a significant influence on the cleaning service performance. (5) Work discipline variables that have the most dominant influence on cleaning service performance.